Habilidade competitiva do feijoeiro e sua tolerância ao herbicida Ethoxysulfuron - Pagnoncelli Junior, Fortunato de Bortoli (2016)
The presence of weeds decreases the crop yield. Among the alternatives to reduce the crop yield loss, it can be included to increase the competitive ability of the crop and the chemical control of the weeds. A research program was developed in the course of Agronomy at Federal Technological University at Paraná, Campus Pato Branco - PR, during the years 2015/16, with the objectives evaluating if gibberellin inhibitors increase the competitive ability of bean plants, making them insensitive to the initialism, extending the period prior to weed-crop interference. Evaluate the tolerance of common bean plants to the herbicide ethoxysulfuron and investigate the existence of relationship between the plant mass and the level of tolerance of the plants to the herbicide. Evaluate the effect of increasing doses of ethoxysulfuron on morphological characteristics, yield components and grain yield of the bean cultivars IPR Tangará and IPR Andorinha. Evaluate the effect of increasing doses of ethoxysulfuron on the development of IAC Imperador and the community of weeds present in the area. Elucidate the mechanism that confers tolerance to bean plants to the herbicide ethoxysulfuron. The results indicate that gibberellin inhibitors were not effective in increasing periods of weed-crop coexistence. Trinexapac-ethyl increased 20% the grain yield of bean plants. It was observed high variability as the response of bean cultivars to the herbicide ethoxysulfuron, however, despite high doses (200 g ha-1), it was not observed death of the plants. The field results indicate that when the ethoxysulfuron dose is 83.2 g ha-1, the reduction in grain yield can reach 40% with the cultivar IPR Tangará and 30% in the cultivar IPR Andorinha. However, respectively for each cultivar cited, ethoxysulfuron at 17 and 12 g ha-1 are enough to reduce 10% of grain yield. Evaluating the control of weeds within the bean crop cultivar IAC Imperador with the herbicide ethoxysulfuron, it was observed that doses at 20 g ha-1 are enough to control soybean and Ipomoea spp. plants. But, due to the level of plant injury, the crop grain yield increase was not sufficient to match the one observed on the weed-free untreated control. The mechanism of tolerance of bean plants to ethoxysulfuron appears to be the herbicide degradation.